2019
DOI: 10.1038/s41598-019-49353-0
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of thickness changes in ten retinal layers of Alzheimer’s disease patients based on optical coherence tomography

Abstract: The retina is an attractive source of biomarkers since it shares many features with the brain. Thickness differences in 10 retinal layers between 19 patients with mild Alzheimer’s disease (AD) and a control group of 24 volunteers were investigated. Retinal layers were automatically segmented and their thickness at each scanned point was measured, corrected for tilt and spatially normalized. When the mean thickness of entire layers was compared between patients and controls, only the outer segment layer of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 66 publications
5
43
1
Order By: Relevance
“…Cell displacement and process reorientation towards an injury site are early features of microglial activation [44,45]. The microglial soma displacement towards the nuclear layers could explain the thickening in some areas of the retinal nuclear layers and the parallel thinning in plexiform layers observed by OCT using a new method for the segmentation of retinal layers in patients with mild AD [11,46]. In addition, it has been postulated that the vertical arrangement of microglial cells, like that of Müller cells, could assist in the distribution of signaling between different microglial plexuses to communicate to the rest of the retina where damage has occurred [6,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell displacement and process reorientation towards an injury site are early features of microglial activation [44,45]. The microglial soma displacement towards the nuclear layers could explain the thickening in some areas of the retinal nuclear layers and the parallel thinning in plexiform layers observed by OCT using a new method for the segmentation of retinal layers in patients with mild AD [11,46]. In addition, it has been postulated that the vertical arrangement of microglial cells, like that of Müller cells, could assist in the distribution of signaling between different microglial plexuses to communicate to the rest of the retina where damage has occurred [6,47].…”
Section: Discussionmentioning
confidence: 99%
“…In AD patients, alterations in the retinal structure detected by Optical Coherence Tomography (OCT) have been reported, suggesting that these alterations could be useful as biomarkers [10][11][12]. According to these studies, in the retina of AD patients, as well as in human postmortem specimens, Aβ plaques have been found from the outer plexiform layer (OPL) to the nerve fiber layer (NFL) [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Two photographs of each eye fundus were obtained using the non-mydriatic retinal camera Canon CR-DGi (Canon Inc., Tokyo, Japan). Optic nerve head (ONH) colorimetric evaluation determined the ONH Hb amount using the Laguna ONhE program, as described in previous studies [20,22,25]. The percentages of the amount of ONH Hb were quantified blindly and independently of the examiner, since the value is automatically provided by the Laguna ONhE program.…”
Section: Optic Nerve Head (Onh) Colorimetric Assessmentmentioning
confidence: 99%
“…Changes in optic nerve head (ONH) reflectance can detect variations in Hb levels, indirectly allowing the assessment of ONH perfusion [20,21]. Laguna ONhE is a program that allows the measurement of ONH perfusion, detecting the pallor caused by a decrease in capillary density and, consequently, axonal loss [22]. Several studies have shown its usefulness in both ocular [22][23][24][25][26] and cerebral [27,28] neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Microvascular changes of the DCP are complemented by the structural thinning of the inner nuclear layer thickness in AD individuals. [40] Changes in the DCP in AD individuals may present later in the disease stage, but a longitudinal study will be required to con rm this hypothesis.…”
Section: Dcp In Ad Individualsmentioning
confidence: 99%